Improving fluency through storytelling in spoken english in third level english students (2020)
Storytelling, Folktales and stories can be used as a tool in order to strengthen fluency, speaking skill and communicative competence. Students of 3rd level at CLE, Universidad del Atlántico, were tested using storytelling, folktales and stories. At the beginning students showed a low level of fluency, speaking skill and reading comprehension and low grammatical competence but after using a social-critical and ethnographic method, pupils were capable of speaking fluently, reading and understanding in a better way. Students of 3rd level at CLE, were aged between 18-22 years old. It was tested a sample of 20 students, 12 boys and 8 girls. These results suggest that with a good methodology and a good disposition, the objectives can be reached.